An Efficient Synthesis of Novel Benzo‐Fused Macrocyclic Dilactams. Issue 7 (12th July 2013) - Mekky, Ahmed E. M.; Ahmed, Ahmed A. M.; Elwahy, Ahmed H. M.
Abstract A facile synthetic approach was adopted towards the synthesis of benzo‐fused macrocyclic lactams 2a–2gvia the base‐catalyzed condensation reaction of 2, 2′‐[alkanediylbis(oxy)]bis[benzaldehydes] 3a–3c with N, N′‐substituted bis[2‐cyanoacetamide] derivatives 7a–7c (Scheme 2). The latter compounds were obtained by the reaction of the appropriate diamines 6a–6c with ethyl 2‐cyanoacetate (4). Attempts to prepare the oxaaza macrocycles 2 by alternative pathways were also investigated. The novel pyrazolo‐fused macrocycles 13a and 13b were obtained in 48 and 52% yield, respectively, upon treatment of 2d and 2g with NH2NH2⋅H2O at 100° (Scheme 4).